2007
DOI: 10.1021/jp072183i
|View full text |Cite
|
Sign up to set email alerts
|

The Mid-IR Spectra of 9-Ethyl Guanine, Guanosine, and 2-Deoxyguanosine

Abstract: We present the mid-IR (400-1800 cm -1 ) spectra of 9-ethyl guanine, guanosine, and 2-deoxyguanosine measured by IR-UV double-resonance spectroscopy. We compare the recorded mid-IR spectra with the spectra of the most stable structures obtained from RI-MP2 and RI-DFT-D calculations. The results confirm the enol form for all structures and demonstrate the efficacy of a new approach to DFT calculations that includes dispersion interactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 27 publications
3
33
1
Order By: Relevance
“…Abo-Riziq et al [94] have reported the mid-IR spectra of the guanine lesion 9-ethylguanine along with guanosine and 2-deoxyguanosine recorded using IR-UV double resonance spectroscopy. Presence of a single isomer of the molecules was demonstrated through resonant two-photon ionization (R2PI) experiments.…”
Section: -Methyl and 9-ethylguaninementioning
confidence: 99%
“…Abo-Riziq et al [94] have reported the mid-IR spectra of the guanine lesion 9-ethylguanine along with guanosine and 2-deoxyguanosine recorded using IR-UV double resonance spectroscopy. Presence of a single isomer of the molecules was demonstrated through resonant two-photon ionization (R2PI) experiments.…”
Section: -Methyl and 9-ethylguaninementioning
confidence: 99%
“…Thus dG •+ and Gs •+ , formed either in the source or from the [Cu II dG 3 ] 2+ and [Cu II Gs 3 ] 2+ precursor complexes, have different structures to those formed from the dimer radical cations. Although this appears to be a novel finding in terms of tautomerisation within gas-phase supramolecular complexes, a search of the literature reveals examples of different gas-phase tautomeric forms of neutral dG and Gs that arise from the way that they are generated in the gas-phase [40][41][42]. Thus IR spectroscopy with resonant two-photon ionisation has been used to show that neutral dG and Gs formed via laser desorption exist in the enol forms D1 and D2 [40], but when hydrated by one or two water molecules, exist in the keto forms C1 and C2 [41,42].…”
Section: Do the Dimeric Radical Cations Have A Unique Structure Contamentioning
confidence: 88%
“…Although this appears to be a novel finding in terms of tautomerisation within gas-phase supramolecular complexes, a search of the literature reveals examples of different gas-phase tautomeric forms of neutral dG and Gs that arise from the way that they are generated in the gas-phase [40][41][42]. Thus IR spectroscopy with resonant two-photon ionisation has been used to show that neutral dG and Gs formed via laser desorption exist in the enol forms D1 and D2 [40], but when hydrated by one or two water molecules, exist in the keto forms C1 and C2 [41,42]. It is also worth mentioning that CID of metal complexes of amino acids and peptides can give rises to isomeric radical cations that depend on the metal complex [43][44][45].…”
Section: Do the Dimeric Radical Cations Have A Unique Structure Contamentioning
confidence: 88%
“…The absorption peaks at 1445 and 1120 cm À1 are due to strong in-plane OH bending mode and C-C stretching vibrations, 80 respectively. The absorption peaks at 2695 and 775 cm À1 correspond to the CH 2 stretching vibrations.…”
Section: View Article Onlinementioning
confidence: 99%